Syllable structure and prosodic words in Early Old French - Rainsford, Thomas M. (Papers in Historical Phonology, 2020)
This paper presents a comprehensive analysis of the phonotactics of syllable rhymes based on all unique tokens in two Early Old French texts. Based on the data from this single, conservative variety, I develop Jacobs’ (1994) proposal that the Old French stress rule is underlyingly trochaic and that word-fiinal stress is caused by the presence of an empty-headed final syllable. I argue that this analysis can only be valid while words with final stress systematically end in a consonant that can, and often must, be parsed as the onset to an empty-headed syllable. Although this is not the case in most later varieties of Old French, the prediction is borne out by our data. I conclude by examining the implications of this analysis for the accentuation and phonotactics of monosyllables and for the study of prosodic change in Old French.